(untitled) (Economic studies journal, 2018)
This research aims to study and identify the effect of Electronic management tools in achieving service quality in Misrata University. Based on analytical descriptive approach through analyzing 100 questionnaires of the university employees. The results of this study demonstrate that there is no statistical correlation between variables, which are using the electronic archiving and computer in saving and recovering data, information and electronic reports in assessing performance as well as attendance and absence system. Therefore, it is a necessity to activate electronic management systems and train the employees to achieve service quality in the university .